Moral disengagement, character strengths, and maladaptive behavior among university students: a structural equation modeling approach - Akhmad Syahri; Nimatul Dinawisda; Sri Afsinatun (International Journal of Evaluation and Research in Education (IJERE), 2026)
The increasing integration of digital technology in higher education has raised concerns about students’ maladaptive behaviors (MB), including academic dishonesty and cyber aggression. This study aims to examine the structural relationships among moral disengagement (MD), character strengths (CS), and MB, as well as the mediating role of CS in digitally mediated learning environments. A cross-sectional quantitative design was employed using data collected from 500 undergraduate students at a State Islamic University in Indonesia through purposive sampling. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that MD significantly predicts MB (β=0.830, p